2019
DOI: 10.21608/svu.2019.12365.1011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Some Virulence Genes in Pseudomonas aeruginosa Isolated from Chicken Embryos and Broilers with regard to Disinfectant Resistance

Abstract: Pseudomonas is a communal motif of environmental associated disease and causes a serious problem in poultry farms, so this study was deliberated to investigate the quandary of Pseudomonas species especially Pseudomonas aeruginosa (P. aeruginosa) which has multifarious virulence genes and plays a major role in poultry outbreaks. Also, it focuses the light on the problem of antimicrobial and disinfectant resistance. A total of 200 samples (100 from dead in shell chicken embryos and 100 from broilers at different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 22 publications
6
20
0
Order By: Relevance
“…Quaternary Ammonium Compounds also are supposed to destruct the outer membrane of Gram-negative microorganism, consequently enhancing their own uptake (McDonnell and Denver 1999). In our study, qacED1 gene was found in all Gram-negative strains (Salmonella, Escherichia coli, and Pseudomonas aeruginosa) with the same 100% percentage, these results agreed with results reported by various workers (Nabil et al 2019;Shahat et al 2019) as they detected qacED1 gene between E. coli, Salmonella, and P. aeruginosa isolates in 100% case. Between the Gram-negative bacteria, QACs resistance genes are frequently associated with plasmid-mediated class 1 integrons that possess a variety of antimicrobial resistance genes.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Quaternary Ammonium Compounds also are supposed to destruct the outer membrane of Gram-negative microorganism, consequently enhancing their own uptake (McDonnell and Denver 1999). In our study, qacED1 gene was found in all Gram-negative strains (Salmonella, Escherichia coli, and Pseudomonas aeruginosa) with the same 100% percentage, these results agreed with results reported by various workers (Nabil et al 2019;Shahat et al 2019) as they detected qacED1 gene between E. coli, Salmonella, and P. aeruginosa isolates in 100% case. Between the Gram-negative bacteria, QACs resistance genes are frequently associated with plasmid-mediated class 1 integrons that possess a variety of antimicrobial resistance genes.…”
Section: Discussionsupporting
confidence: 92%
“…In another report, P. aeruginosa strains isolated from 216 yolk sacs of baby chicks were resistant to florfenicol (El-Sawah et al 2016). All P. aeruginosa isolates recovered from the liver, heart, and yolk sacs of 50 samples of baby chicks were 100% resistant to ampicillin (Shahat et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to each antibiotic caused a decreased level of biofilm expression ranging between 0.1-and 0.7-fold changes, while the repression was strong and most significant with amikacin-cefotaxime combination treatment with fold change reaching 0.08, i.e., the consequence of treatment on the average expression profile among all biofilm involving genes constituting the bacterial communities studied. As described in this paper and by others [59][60][61], sub-MICs of combinations have potent effects on attenuating biofilm formation which are totally different from each antibiotic alone.…”
Section: Discussionmentioning
confidence: 64%
“…According to the results, PCR asserted the presence of P. aeruginosa DNA in all the selected isolates identified conventionally. The confirmation of P. aeruginosa identification via molecular approach turned out to be increasingly imperative to diminish the issues of culture method such as a false negative culture result that may be owing to the sample overgrowth by other bacteria (Shahat et al 2019). Of the acquired metallo-βlactamase genes investigated, NDM-1 had been the most frequently detectable gene among the selected XDR-PA isolates, although the rare occurrence in Egypt.…”
Section: Discussionmentioning
confidence: 99%